A previously undescribed cranial surgery technique in the Carpathian Basin 10th century CE. (11th January 2022) - Kis, Luca; Tihanyi, Balázs; Király, Kitty; Berthon, William; Spekker, Olga; Váradi, Orsolya Anna; Nagy, Réka; Neparáczki, Endre; Révész, László; Szabó, Árpád; Pálfi, György; Bereczki, Zsolt
Abstract: In this paper, the authors give a new insight to the indication and preparation of trepanations through the analysis of a newly discovered case of 10th‐century‐CE surgical trepanation found in the material of Sárrétudvari‐Poroshalom. We also intend to outline the implications of this particular case to the general methodology of trepanation research. We estimated basic anthropological data (sex and age‐at‐death) and performed analyses of paleopathological and activity‐related lesions. Computed tomography, radiocarbon, and genetic analyses were also conduced. Beside other prior traumas, two codependent lesions were detected on the right parietal bone with no sign of healing. In this lesion complex, an original sharp force trauma was observable surrounded by two curved, intentionally created furrows, which can be interpreted as attempted surgical trepanation presumably performed with a U‐shaped gouge. The results of the analysis of activity‐related changes and archeological examination corroborate the assumption that the injuries described on the skull may have been, indeed, acquired during activities connected to military lifestyle, and the individual may have been a high‐ranking military leader in his community. This unique case has paramount importance providing more detailed knowledge of past medical practices. The application of U‐shaped gouge has not been formerly documented in the literature, which opens a new perspective both in the osteological investigation of these interventions and the archeological research concerning ancient medical technology. Our results may suggest a possible mode of tool use, and aid future reconstruction attempts concerning the hypothesized 10th‐century‐CE trepan from Tiszaeszlár–Bashalom.